Study on Short-lived Climate Pollutants in Hanoi in the Context of Climate Change and Sustainable Development - Đỗ, Duy Tùng (2020)
Simultaneous observation of black carbon (BC), tropospheric ozone (TO3) and particulate matter 2.5 (PM2.5), which are significant climate forcers, was carried out at Hanoi to clarify the concentrations and variations of Short-lived Climate Pollutants (SLCP) in Hanoi and Northern Vietnam. The research applied HYSPLIT trajectory model to distinguish contribution source regions of SLCPs to Hanoi. Since we cannot use remote sensing for aerosol optical depth (AOD) analysis during wintertime, especially January, due to thick cloud coverage over Hanoi, we deployed remote PM2.5 stations surrounding Hanoi and coastal region in Northeast sector of Northern Vietnam to compare upwind/downwind concentrations. The results showed monthly average of BC, daytime TO3 and PM2.5 as 1-3μg/m3, 21-55ppbv, 18-65μg/m3, accordingly. Both BC and PM2.5 were remarkably increased during rush hours or night-time in diurnal variation. In contrast, TO3 was often high at noon and depleted to zero at night. These diurnal variations can be attributed to their local/regional emissions and production of them near Hanoi. The climax episodes of BC and PM2.5 were observed in wintertime, especially in January with periods lasting from 1 day to 1 week. These high rises were mostly associated with winter monsoon trajectories from South China Sea, which actually transported emissions from North East region of Northern Vietnam. These results firstly show a large contribution of Northern Vietnam sources of SLCP to their concentrations. Given the significant climate forcing of BC, this study strongly suggests that mitigation measures to reduce BC in Vietnam can considerably improve both regional climate change and air quality in the Northern Vietnam region.